Extracellular BSA-degrading SAPs in the rare pathogen of Meyerozyma guilliermondii strain SO as potential virulence factors in candidiasis - Oslan, Siti Nurbaya; Salleh, Abu Bakar; Mohamad Ali, Mohd Shukuri; Sabri, Suriana; Muhd Noor, Noor Dina; Si, Jie Lim (Academic Press, 2024)
Meyerozyma guilliermondii (Candida guilliermondii) is one of the Candida species associated with invasive candidiasis.With the potential for expressing industrially important enzymes, M. guilliermondii strain SO possessed 99% proteome similarity with the clinical ATCC 6260 isolate and showed pathogenicity towards zebrafish embryos. Recently, three secreted aspartyl proteinases (SAPs) were computationally identified as potential virulence factors in this strain without in vitro verification of SAP activity. The quantification of Candida SAPs activity in liquid broth were also scarcely reported. Thus, this study aimed to characterize M. guilliermondii strain SO’s ability to produce SAPs (MgSAPs) in different conditions (morphology and medium) besides analyzing its growth profile. MgSAPs’ capability to cleave bovine serum albumin (BSA) was also determined to propose that MgSAPs as the potential virulence factors compared to the avirulent Saccharomyces cerevisiae. M. guilliermondii strain SO produced more SAPs (higher activity) in yeast nitrogen base-BSA-dextrose broth compared to yeast extract-BSAdextrose broth despite insignificantly different SAP activity in both planktonic and biofilm cells. FeCl3 supplementation significantly increased the specific protein activity (~40 %). The BSA cleavage by MgSAPs at an acidic pH was proven through semi-quantitative SDS-PAGE, sharing similar profile with HIV-1 retropepsin. The presented work highlighted the MgSAPs on fungal cell wall and extracellular milieu during host infection could be corroborated to the quantitative production in different growth modes presented herein besides shedding lights on the potential usage of retropepsin’s inhibitors in treating candidiasis. Molecular and expression analyses of MgSAPs and their deletion should be further explored to attribute their respective virulence effects.